2019
DOI: 10.1182/bloodadvances.2019000445
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent genetic HLA loss in AML relapsed after matched unrelated allogeneic hematopoietic cell transplantation

Abstract: Immune evasion is a hallmark of cancer and a central mechanism underlying acquired resistance to immune therapy. In allogeneic hematopoietic cell transplantation (alloHCT), late relapses can arise after prolonged alloreactive T-cell control, but the molecular mechanisms of immune escape remain unclear. To identify mechanisms of immune evasion, we performed a genetic analysis of serial samples from 25 patients with myeloid malignancies who relapsed ≥1 year after alloHCT. Using targeted sequencing and microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 37 publications
2
47
0
1
Order By: Relevance
“…This suggests that in these patients, major HLA mismatches were the critical targets of the GvL response and loss of mismatched HLA as a single large-scale genetic event was sufficient to evade immune detection. Genomic HLA loss has also been described following HLA-matched allo-SCT for AML (101, 102). In a recent study of relapsed AML in 12 recipients of matched unrelated donor transplants, 2 patients were found to have focal deletions spanning HLA class I alleles.…”
Section: Evidence For a Gvl Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that in these patients, major HLA mismatches were the critical targets of the GvL response and loss of mismatched HLA as a single large-scale genetic event was sufficient to evade immune detection. Genomic HLA loss has also been described following HLA-matched allo-SCT for AML (101, 102). In a recent study of relapsed AML in 12 recipients of matched unrelated donor transplants, 2 patients were found to have focal deletions spanning HLA class I alleles.…”
Section: Evidence For a Gvl Effectmentioning
confidence: 99%
“…Given that HLA alleles were identical in patient and donor, it is likely that the pivotal GvL targets were peptide(s) presented by HLA. In this setting, loss of the HLA locus prevented these key peptides being presented to donor-derived T cells (102).…”
Section: Evidence For a Gvl Effectmentioning
confidence: 99%
“…Taffalori et al identified a transcriptional signature specific for post-transplantation relapses, highly enriched in immune-related processes; in parallel, it was documented a deregulation of multiple co-stimulatory ligands, such as PD-L1, CD80 and PVRL2, on AML blasts al post-transplantation relapse and frequent loss of HLA-DR, -DQ and -DP expression on leukemic cells due to downregulation of the HLA class II regulator CIITA [31]. Furthermore, HLA loss was reported in 12% of patients relapsing after allo HSCT and seems to be an event related to stem cell transplantation in that it is observed in only 0.2–1% of non-transplantation AML cohorts; furthermore, HLA-loss was not observed after matched related-donor HSCT [32]. Finally, Noviello et al provided evidence that in post-transplantation relapsing patients a higher proportion of bone marrow infiltrating T lymphocytes express inhibitory receptors, such as PD-1, CTLA4, TIM-3 and LAG-3 [33].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Noviello et al provided evidence that in post-transplantation relapsing patients a higher proportion of bone marrow infiltrating T lymphocytes express inhibitory receptors, such as PD-1, CTLA4, TIM-3 and LAG-3 [33]. Interestingly, some of the immune defects of post-transplantation AMLs can be reversed by IFN-γ or by immune checkpoint inhibitors [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of pathways involved in T cell-mediated allorecognition has been identified as a feature and driver of AML relapses after allo-HCT, 65 including downregulation of major histocompatibility complex class II genes involved in antigen presentation, loss of HLA class I antigens in the case of HLA-matched and HLA-mismatched transplants, and the acquisition of de novo mutations. [66][67][68] These changes potentially offer insights that could eventually be translated into personalized therapies.…”
Section: Combination Of Allogeneic Cell Transplantation With Immunothmentioning
confidence: 99%